'Cegah 3 serangkai sebelum berangkai'. Health fest post-COVID-19 pandemic - Chen, Xin Wee; Mat Ruzlin, Aimi Nadira; A. Rashid, Nurul Syaireen; Ramli, Siti Ramizah; Mohd Saad, Noraini; Mohamad, Mariam (Faculty of Medicine, 2023)
The UiTM Health Fest 2023 with the theme 'Cegah 3 Serangkai Sebelum Berangkai' was held on the 20th of August 2022 in Dewan Teratai, Seksyen 19 in Shah Alam and attended by more than 150 community participants. The carnival was coordinated by fourth year medical students from the Faculty of Medicine, UiTM Sungai Buloh in collaboration with Majlis Perwakilan Penduduk Zon 7 and Majlis Bandaraya Shah Alam (MBSA). The carnival was officiated by Assoc. Prof. Dr. Effat Binti Omar (Deputy Dean Academic, Faculty of Medicine UiTM) and Tuan Hj Jamil (Head of Majlis Persatuan Penduduk Zon 7, Shah Alam). Also in present, Tuan Ahmad Syahid Bin Samsijan (Representative of Majlis Bandaraya Shah Alam), Assoc. Prof. Dr Mariam binti Mohamad (Head of Department Public Health Medicine, Faculty of Medicine), Assoc. Prof. Dr Ahmad Taufik Jamil (Year 4 PHPM posting Coordinator), and Nor Aidil Adha bin Abdullah Sani (Health Program Director).